Superconducting properties and surface roughness of thin Nb samples fabricated for SRF applications. (June 2020) - Ries, R; Seiler, E; Gömöry, F; Medvids, A; Pira, C; Malyshev, O B
Abstract: Using a thin Nb layer on Copper substrate has several advantages compared with the bulk Nb in construction of Superconducting Radiofrequency accelerating cavities (SRF) for particle accelerators. We were evaluating the properties of two series of Nb layers deposited on Cu substrate, mainly by determining the start of magnetic flux penetration into the sample – the first magnetic flux entry field B en, proportional to the B c1 . The values of B en are compared with the surface roughness and surface morphology of the Nb layers, which have a strong influence on B en . The surfaces of the samples were also treated by Nd:YAG laser depending on laser irradiation dose. The results of B en and surface roughness before and after laser polishing are compared.